2012 IEEE International Reliability Physics Symposium (IRPS) 2012
DOI: 10.1109/irps.2012.6241868
|View full text |Cite
|
Sign up to set email alerts
|

The scaling of electromigration lifetimes

Abstract: The reduction of electromigration failure times with scaling presents a critical challenge for continued technology development. Electromigration failure is determined by void morphology and Cu drift velocity. Using observations of changes in these parameters, particularly the increase in drift velocity due to the increasingly polycrystalline Cu grain structure, we are able to accurately model trends in failure times between the 65 and 20 nm nodes. Below 20 nm failure times will continue to decrease, but at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…We have shown that void volumes measured during accelerated testing are independent of technology nodes 65 to 20 nm despite significant changes in the Cu microstructure in this range. 2 Therefore, failure times are controlled primary by the Cu drift velocity, which is determined by the nature of the diffusion pathways for the conductor, and is, therefore, sensitive to the details of the Cu microstructure. In the next section we discuss in detail how the Cu microstructure determines the drift velocity.…”
Section: Influence Of Cu Microstructure On Electromigration Failurementioning
confidence: 99%
“…We have shown that void volumes measured during accelerated testing are independent of technology nodes 65 to 20 nm despite significant changes in the Cu microstructure in this range. 2 Therefore, failure times are controlled primary by the Cu drift velocity, which is determined by the nature of the diffusion pathways for the conductor, and is, therefore, sensitive to the details of the Cu microstructure. In the next section we discuss in detail how the Cu microstructure determines the drift velocity.…”
Section: Influence Of Cu Microstructure On Electromigration Failurementioning
confidence: 99%
“…4. Unlike the typically observed slit void failure mode [10][11][14][15][16][17] from downstream EM test, physical failure analysis revealed trench void for both downstream and upstream stress, as shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 83%
“…Due to the decrease of critical feature size with scaling, as well as changes in the microstructure of the Cu, failure times have decreased significantly with technology scaling [76][77][78]. This reduction poses a serious challenge to attaining the increasing current densities required for continued performance enhancement and density increase.…”
Section: Electromigrationmentioning
confidence: 99%